2014
DOI: 10.14740/wjon778w
|View full text |Cite
|
Sign up to set email alerts
|

Amylase-Producing Lung Cancer with a Positive Epidermal Growth Factor Receptor Mutation Treated With Gefitinib: A Case Report

Abstract: A 60-year-old woman was diagnosed with metastatic pulmonary adenocarcinoma (c-stage IV) with an L858R point mutation in the gene encoding epidermal growth factor receptor (EGFR). Serum amylase levels were elevated (1,531 IU/L) with the salivary-type enzyme dominating. First-line chemotherapy using carboplatin plus paclitaxel reduced serum amylase levels, although second-line gefitinib eventually failed to control tumor growth and hyperamylasemia after 4.5 months of treatment. The cancer cells harbored a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Amylase-producing lung tumors were first reported in 1951, 12 and they are pathologically characterized by adenocarcinoma and the secretion of salivary-type amylase. Previous reports indicated that the increase in serum CEA was not observed in amylase-producing lung adenocarcinoma 13 at the point of diagnosis. Interestingly, the CEA levels gradually increased in spite of treatment, whereas the amylase levels decreased.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Amylase-producing lung tumors were first reported in 1951, 12 and they are pathologically characterized by adenocarcinoma and the secretion of salivary-type amylase. Previous reports indicated that the increase in serum CEA was not observed in amylase-producing lung adenocarcinoma 13 at the point of diagnosis. Interestingly, the CEA levels gradually increased in spite of treatment, whereas the amylase levels decreased.…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, two case reports on amylase-producing tumors harboring an EGFR-mutations. 13 , 14 Interestingly, amylase secretion by rat pancreatic cells is thought to be regulated by EGFR downstream signaling. 15 The relationship between ALK -rearranged NSCLC and amylase-producing lung adenocarcinoma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our study showed that EGFR-positive lung adenocarcinoma tended to have higher pleural amylase levels than EGFR-negative cancer; however, the relationship between amylase secretion and EGFR mutations is uncertain (16). The EGFR gene is an oncogenic driver of tyrosine kinase activity, and EGFR has been identified as an oncogenic driver of non-small-cell lung carcinoma (NSCLC) (17).…”
Section: Discussionmentioning
confidence: 87%
“…In addition to that, α-AMY has been identified in cases of lung cancer (12) , breast cancer, and ovarian cancer (13) . α-AMY inhibitors, commonly known as starch blockers, may offer possible mitigation by inactivating Amylase in saliva or pancreatic digesting juice, lowering blood glucose.…”
Section: Introductionmentioning
confidence: 99%